TRANSLATION OF SPECIAL TEXTS IN DIFFERENT STYLES, COMPUTER TRANSLATION - Akhnazarov Abdulazizbek Boyxo’roz o’g’li; Zilola Abdurakhmanova Yoqubjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: In the ever-expanding global landscape, the demand for accurate and efficient translation services has grown exponentially. The realm of computer translation, powered by sophisticated algorithms and artificial intelligence, plays a pivotal role in this arena. This article delves into the intricacies of translating specialized texts across different styles using computer translation, exploring both the advancements and challenges in this dynamic field.